Теоретико-ігрова модель боротьби партій за электорат - Nedashkivskya, N. I.; Ostapenko, V. V.; Ostapenko, O. S. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
А model to be used by parties during election campaign to define finances distribution among the regions to get a maximal advantage is proposed. Conditions under which the model can be referred to a convex game are defined. The conclusions resulted from the research proved true during the parliament elections in 2002.